Pemberdayaan Masyarakat Sekitar TPA (Tempat Pembuangan Akhir) Dalam Pemanfaatan Sampah Non Organik Menjadi Kerajinan Untuk Meningkatkan Nilai Jual - Moh. Mahmud; Sugiyono Sugiyono; Sumari Mawardi; Munawir Munawir (IAI Darussalam, 2019)
This paper provides an overview of the condition of the community around the TPA (Final Waste Disposal Site) of Sumberejo hamlet Wringinagung Village Gambiran District Banyuwangi Regency in processing non-organic waste into handicrafts that have more selling value to improve the community's economic level. The community service approach used is PAR (Participatory Action Research) in the form of community training and training. The results of this dedication show the enthusiasm of the community to be able to participate in these activities and practice them in order to get more economic resources and meet their daily needs